The Impact of Smartphone Use on the Psychology of Young Children in Parungponteng District - Riza Andrian Ibrahim; Astrid Sulistya Azahra; Nurnisaa binti Abdullah Suhaimi (Research Collaboration Community (RCC), 2024)
This research aims to analyze the impact of gadget use on the psychological development of elementary school-aged children at Cibuntu Elementary School, Cibungur Village, Parungponteng District. The research method used is a qualitative approach using observation, questionnaires and interviews as data collection techniques. The research results show that the use of gadgets has both positive and negative impacts on children's psychological development. Positive impacts include improved cognitive skills and access to information, while negative impacts include the risk of addiction and behavioral disorders. The role of parents and schools in supervising and directing gadget use is very important to minimize negative impacts. This research provides a comprehensive picture of the complexity of the interaction between technology and child development.